Seed quality and relative lignan profiles of sesame prospected from northern Ghana - Henry Ofosuhene Sintim (Heliyon)
The sesame seed contains oil, protein, dietary fibre, and several minerals and it is also a store of lignans. Lignans are key selection factors for sesame quality due to their health, nutritive and market value. In Ghana sesame growers rely on wild or undocumented planting seeds which are of mixed colouration and its lignan content is ambiguous. The objective of this study was to segregate street sesame seeds into component colour fractions and subsequently evaluate the consistency of lignans in the seed fractions. Sesame seeds were collected from street vendors in northern Ghana and were segregated into seed fractions based on the pericarp colour. The viability of seed fractions stored at different temperatures (ambient, 5 °C, 0 °C) over time and lignan contents of single or bulk mixed seeds were verified. The collected seeds were of mixed colouration with approximately 4 % debris, 40 % white, 36 % cream, and 20 % dark coloured seeds by weight. The viability of the seeds was 67–85 % depending on pericarp colour. White seed fractions which had the highest proportion by weight had a significantly (p = 0.0275) higher viability (85 %) than the dark seeds which had the least viability (67 %). The seeds lost viability over time. However, seeds stored at 0 °C maintained a viability of 77 % at the fourth year. There were differences in the relative abundance of lignans for both bulk seeds and, single seeds with different pericarp colours. The most abundant occurring lignans in the seeds were sesamin, sesamolin and sesaminol and its downstream glucosides. The source of seed or pericarp colour was not predictive of seed viability or lignan composition. These findings provide baseline data on seed quality including an improved storability under cold environments. It also gives an insight into how mixed seeds of variable pericarp colours can have distinct characteristics. Although the mixed coloured seeds had no implications for varied quality including lignan content, the international market for sesame requires that seeds are of consistent colour.